Diagnóstico de la situación actual del sector cacaotero en función de la asesoría técnica y el financiamiento en el recinto Concepción perteneciente al cantón Baba Provincia de Los Ríos - Luis David Chica Moran (2020)
The agricultural activity dedicated to the cultivation of cocoa (Theobroma cacao L) is constituted as one of the main products that generates the highest income for peasant families, in addition to being an important item within the trade balance of Ecuador. The province of Los Ríos is one of the most privileged agricultural areas in Ecuador, it has a predominantly rural population, with agricultural production being its main economic activity. Due to the soil conditions that are excellent for export crops such as cocoa, which makes it currently occupy the first place as a cocoa producer in the country, becoming the main source of production in the region. In order to develop this document, ten cocoa farmers belonging to the new Concepción del Cantón Baba were surveyed in order to determine the need for technical advice and financing. The surveys were made up of closed questions, which were tabulated and whose results can be seen in Chapter II of this document, information was also obtained from books, magazines, newspapers, scientific articles, web pages, presentations that were subjected to the technique of analysis and summary with the subject referring to the study carried out. The conclusions determine the lack of access to technology, training and financing for the cocoa farmers of the recent Concepción, belonging to the Baba Canton, which have caused the crop yields to fall, which makes the possibility of a modernization of their cocoa farms difficult to increase productivity levels. Therefore, it is recommended to the governmental institutions of the agricultural sector that through the different programs that the producers have, they can access the training so that they obtain solid knowledge bases in the development processes of the crop and that they also associate so that can receive greater benefits such as access to credit and technical advice.